Models for Moody's bank ratings - Anatoly Peresetsky; Alexander Karminsky (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
The paper presents an econometric study of the two bank ratings assigned by Moody's In-vestors Service. According to Moody s methodology, foreign-currency long-term deposit ratings are assigned on the basis of Bank Financial Strength Ratings (BFSR), taking into account external bank support factors (joint-default analysis, JDA). Models for the (unobserved) external support are presented, and we find that models based solely on public information can reasonably well approximate the ratings. It appears that the observed rating degradation can be explained by growth of the banking system as a whole. Moody s has a special approach for banks in developing countries and Russia in particular. The models help reveal the factors that are important for external bank support.
URN:NBN:fi:bof-201408072122
Keywords: 330